"A life of living death": the experiences of people living with chronic low back pain in rural Nigeria. Issue 8 (10th April 2017) - Igwesi-Chidobe, Chinonso N.; Kitchen, Sheila; Sorinola, Isaac O.; Godfrey, Emma L.
Abstract: Purpose : This study explored the experiences of people living with non-specific chronic low back pain (CLBP) in a rural Nigerian community. Method : Qualitative in-depth semi-structured face-to-face interviews were conducted with purposively sampled participants until data saturation. Questions explored back pain beliefs, coping/management strategies and daily activities. Thematic analysis of transcripts was performed using the Framework approach. Results : Themes showed that back pain beliefs were related to manual labour/deprivation, infection/degeneration, spiritual/cultural beliefs and rural–urban divide. These beliefs impacted on gender roles resulting in adaptive or maladaptive coping. Adaptive coping was facilitated by positive beliefs, such as not regarding CLBP as an illness, whereas viewing CLBP as illness stimulated maladaptive coping strategies. Spirituality was associated with both adaptive and maladaptive coping. Maladaptive coping strategies led to dissatisfaction with health care in this community. Conclusions : CLBP-related disability in rural Nigeria is strongly influenced by beliefs that facilitate coping strategies that either enhance or inhibit recovery. Interventions should therefore target maladaptive beliefs while emphasizing behavioural modification. Implications for Rehabilitation: Non-specific chronic low back pain (CLBP) is highly prevalent and responsible for much pain and disability in rural Nigeria. No qualitative study has investigated the experiences of people living with CLBP in rural Nigeria or any other rural African context. Qualitative study of peoples' experiences of living with CLBP in rural Nigeria has the potential of exposing complex socio-cultural and psychological factors associated with CLBP which has potential implications for designing effective interventions. The results of this study may inform the development of complex interventions for reducing the disability associated with CLBP in rural Nigeria and other rural African contexts.